Assessment of Urothelial Cytotoxicity at Morphological and Molecular Levels: Urinary Bladder as Target Organ - Lima, Thania Rios Rossi [UNESP]; Sales, Bianca Camargo Penteado [UNESP]; Catalano, Shadia Muhammad Ihlaseh (Springer Nature, 2021)
The urinary bladder is a target organ of several toxic agents. Exposure to those agents induces mild-to-severe changes, which can be evaluated by different methods. Among them, the scanning-electron microscopy (SEM) is the “gold standard” for characterizing urothelial damage since it provides high-definition images, making it possible to detect early lesions on the surface of the urinary bladder. In addition, molecular technologies allow detecting changes in genetic material and investigating the interaction between genes and environmental stress in disease causation. The urinary bladder epithelium is where the most common type of bladder cancer occurs in humans, that is, the transitional-cell carcinoma (TCC). In animal models, the TCC can be similar to the disease in humans. Techniques to evaluate urothelium in experimental models aid in the comprehension of risk factors for urothelial carcinogenesis.
Keywords: Cytotoxicity; Epithelial cells; In vivo; Molecular biology; Scanning-electron microscopy; Urinary bladder